[PP.33.02] FORWARD AND BACKWARD PRESSURE WAVEFORM MORPHOLOGY IN HYPERTENSIVE SUBJECTS. (September 2016) - Li, Y.; Gu, H.; Fok, H.; Alastruey, J.; Chowienczyk, P.
Abstract : Objective: Beyond middle age hypertension results mainly from an increase in pulse pressure which may be attributed to a forward pressure wave generated by the interaction of the ventricle with the arterial tree and a backward wave due to "reflection" of the forward wave. We investigated whether increased pulse pressure in hypertension relates to a proportionally greater backward/forward wave or is driven by an increase in the forward wave. Design and method: Non-invasive central pressure and flow were obtained by carotid tonometry and Doppler sonography respectively in 158 hypertensive patients (mean ± SD age, 46 ± 17 years). Patients were divided into three groups by pulse pressure (group 1: 29.7 ± 5.3, group 2: 41.5 ± 2.6, group 3: 60.1 ± 12.5 mmHg). Forward and backward pressure waves were separated using wave intensity analysis. Dimensionless ratios were used to examine how characteristics of the backward wave: maximum amplitude, slope of upstroke, width at 80% maximum and area compared to the same characteristics of the forward wave. Results: All the dimensionless ratios were similar across the three groups, with no statistically significant difference in any ratio. However, the backward wave provided a slightly greater contribution to central pulse pressure in group 3 compared to group 1 (20.2 ± 1.3% vs. 16.3 ± 1.8%, means ± SE due to earlier time of arrival of the backward wave: 95 ± 2.8 vs. 107 ± 5.2 ms, P < 0.05). Conclusions: Increased pulsatile components of blood pressure in hypertension derive predominantly from the interaction of ventricular contraction with the impedance of the arterial tree. "Reflection" of the backward wave remains approximately the same across groups with a two-fold difference in pulse pressure. Earlier arrival of the backward wave contributes to a small proportion of the increase in pulse pressure.